2018
DOI: 10.1111/phpp.12430
|View full text |Cite
|
Sign up to set email alerts
|

The impact of positive antinuclear antibody on narrowband ultraviolet B phototherapy in patients with vitiligo: A retrospective chart review

Abstract: Summary Background/Purpose Screening antinuclear antibody (ANA) is not recommended prior to initiating narrowband ultraviolet B (NBUVB) phototherapy in vitiligo patients, unless concern for photosensitivity exists. Guidelines on prescribing NBUVB phototherapy in vitiligo patients with positive ANA are unavailable, prompting this study to uncover trends. Methods This retrospective chart review investigated patients 12 years of age or older with a diagnosis of vitiligo between January 2015 and September 2017, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These patients could not tolerate the expected doses that were usual for their skin phototypes. The researchers consequently postulated that ANA might be a variable contributor to photosensitivity in vitiligo patients 8 . However, their study represented a small number of patients and did not exclude the history of concurrent photosensitizing medication.…”
Section: Discussionmentioning
confidence: 99%
“…These patients could not tolerate the expected doses that were usual for their skin phototypes. The researchers consequently postulated that ANA might be a variable contributor to photosensitivity in vitiligo patients 8 . However, their study represented a small number of patients and did not exclude the history of concurrent photosensitizing medication.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that their study consisted of a small number of patients and did not exclude the patients on concurrent photosensitizing medication. Based on the findings of their study, the authors concluded that status of ANA may not be exclusionary criteria when prescribing NBUVB, but a positive ANA might contribute to emergence of photosensitivity in vitiligo patients; therefore, dose adjustment should be done with caution 22 . Based on the results of this study and our study, it may be suggested that screening of ANA before NB‐UVB phototherapy is not necessary unless there are symptoms and signs of autoimmune diseases and ANA positivity without any symptoms should not be exclusion criteria for NB‐UVB phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Routine ANA screening before vitiligo phototherapy therefore is not recommended unless clinical symptoms of other autoimmune diseases are present, and if a patient is showing new-onset photosensitivity after initiation of NBUVB. 3,[163][164][165]…”
Section: Phototherapy and Screening For Anti-nuclear Antibodies In Pa...mentioning
confidence: 99%
“…Also, prior ANA positivity wasn't linked to phototoxic reactions or predictive of development of SLE in vitiligo patients undergoing phototherapy. Routine ANA screening before vitiligo phototherapy therefore is not recommended unless clinical symptoms of other autoimmune diseases are present, and if a patient is showing new‐onset photosensitivity after initiation of NBUVB 3,163–165 …”
Section: Miscellaenousmentioning
confidence: 99%